2007
DOI: 10.1007/s11251-007-9020-y
|View full text |Cite
|
Sign up to set email alerts
|

Block scheduled versus traditional biology teaching—an educational experiment using the water lily

Abstract: In this study, we compared a traditional teaching sequence (four distinct lessons) with a block schedule dealing with the ecological adaptations of the water lily. The educational unit contained original plant material and both experimental groups received the same tasks and working sheets. Pupils worked together in groups of three to four pupils in a self-regulated manner, carrying out hands-on experiments. However, both groups differed in their time schedule (four distinct lessons of 45 min versus one block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…This is in spite of the research that has been done over time. Much of the research goes back as far as the 1960s, comparing various forms of intensive courses to traditional delivery, and has found that there was mostly no difference in the learning outcomes between these two modes of delivery, with some studies that found intensive courses were more favorable in certain disciplines (the biological sciences was not one of these) and a few studies that found traditional mode teaching was superior (Mims, ; Scott and Conrad, ; Van Scyoc and Gleason, ; Hutchinson and Martin, ; Lawrence and McPherson, ; Spurling, ; Burton and Nesbit, ; Davies, ; Randler et al, ; Ho and Polonsky, ; Laves, ; Ramsay, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in spite of the research that has been done over time. Much of the research goes back as far as the 1960s, comparing various forms of intensive courses to traditional delivery, and has found that there was mostly no difference in the learning outcomes between these two modes of delivery, with some studies that found intensive courses were more favorable in certain disciplines (the biological sciences was not one of these) and a few studies that found traditional mode teaching was superior (Mims, ; Scott and Conrad, ; Van Scyoc and Gleason, ; Hutchinson and Martin, ; Lawrence and McPherson, ; Spurling, ; Burton and Nesbit, ; Davies, ; Randler et al, ; Ho and Polonsky, ; Laves, ; Ramsay, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear exactly how this relates to intensive mode delivery, as there is also research that shows intense immersion in a subject is beneficial to students in some subjects. Further, although it is intuitive to think that less allocated time would impoverish learning, it has been shown to be only a modest predictor of achievement, as other factors relating to the quality of teaching and productive use of time are also important (Scott and Conrad, ; Burton and Nesbit, ; Wlodkowski, ; Randler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the findings of [116] that teachers' ASCs are indicators of their achievements in professional knowledge, the results on RQ 2 are used to assess the external validity of the cognitive test (see Section 2.4.1). Furthermore, studies on the effects of the course format (weekly versus block course format) are mostly situated in the context of schooling [152,170]. Few research reports relate to higher education teaching (see Section 1.4; [150]).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…However, it is more important to examine the differences in terms of long-term CK retention, as "retention is considered the more serious test because it shows which knowledge is retained or stable over longer time periods" ( [170], p. 21). If it turns out that block course participants lose a lot of CK from the course after six months, it is questionable to offer this course format, as it usually still takes time for them to apply the knowledge in professional practice.…”
Section: Impact Of the Course Formatmentioning
confidence: 99%
“…After 5 days, participants who received the distributed sessions outperformed participants who received the sessions in a massed fashion in free and cued recall with an increase of 13% and 14%, respectively. In a more recent study, Randler et al (2008) investigated blocked vs. traditional teaching in biology class. The traditional condition received four lessons of 45 min each in a weekly schedule, while in the blocked condition, the students received all lessons within one morning.…”
Section: Distribution Of Text Reading As Special Case Of Distributed Practicementioning
confidence: 99%